Implementation of community economic empowerment by utilizing yards based on organic vegetable planting with an environmental perspective - Nurzam Nurzam; Yesi Indian Ariska; Iswidana Utama Putra; Rinto Noviantoro; Anzori Anzori (Privietlab, 2022)
Community empowerment is one of the strategies in efforts to implement community development based on the principle of democracy, in which the community is encouraged to place itself proportionally and become the main character in improving their own standard of living by accessing and utilizing available resources on a sustainable basis. Empowering the community through the use of yards program activities are one of the efforts that can be made to increase accessibility and availability of food independently and sustainably, and is oriented towards increasing community's income. RT 32 RW 07 Sawah Lebar Village in Bengkulu City is one of the potential areas for the development of organic farming-based yard utilization program, but it has not been optimally implemented due to several constraints, including the lack of knowledges, lack of facilities and infrastructure in producing their own fertilizer. Therefore, through community service activities, it is expected to be able to support and increase food self-sufficiency and the community's economy. This activity was carried out on October 8 2022 at RT 32, RW 07, Sawah Lebar Village, Bengkulu City. In this activity several stages of activity were used, namely planning and preparation, socialization about optimizing the use of yard land, and demonstrations of making compost and liquid organic fertilizer, as well as assistance in planting good commodities to be planted in the yard. This program was attended by residents and the local village government. Activities carried out concurrently between socialization and training in making compost and liquid organic fertilizer through presentation of material accompanied by discussions related to optimizing yards. From the results of the implementation of this activity it can be concluded that community economic empowerment can be carried out through optimizing the yard by planting vegetables and medicinal plants as an effort to support the availability of food and family medicines, as well as being useful for adding environmental aesthetic value, family hobbies, as well as the preservation of biological resources and the environment.